2010
DOI: 10.1007/s11661-010-0532-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Yttrium on Ti-5111 Gas Tungsten Arc Welds

Abstract: Much interest has developed in the near-a titanium alloy Ti-5Al-1Sn-1V-1Zr-0.8Mo (Ti-5111) for naval applications. When gas tungsten arc welded with filler metal that has the same chemical composition as the base metal, however, the weld FZ tends to be harder and less ductile than the base metal, which may make the weld susceptible to failure. This behavior may be attributed to the presence of oxygen impurities and the large prior-b grain size in the weld. In this investigation, the addition of a small amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The second type of particle contains sulfur in addition to titanium (e.g., Figure 7). The scavenging of sulfur by Y 2 O 3 in titanium and other systems has been reported elsewhere [31][32][33] and is not the focus of this study. Finally, a small number of particles contains neither chlorine nor sulfur (here termed NCS particles) and have a composition that closely matches that of Y 2 O 3 .…”
Section: B Liquid Phase Sinteringmentioning
confidence: 94%
“…The second type of particle contains sulfur in addition to titanium (e.g., Figure 7). The scavenging of sulfur by Y 2 O 3 in titanium and other systems has been reported elsewhere [31][32][33] and is not the focus of this study. Finally, a small number of particles contains neither chlorine nor sulfur (here termed NCS particles) and have a composition that closely matches that of Y 2 O 3 .…”
Section: B Liquid Phase Sinteringmentioning
confidence: 94%
“…More specifically, Neuberger, et al's recent approach to improve the FZ ductility was to modify the weld filler metal by adding small concentrations of yttrium (Y) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier reported results, Neuberger, et al [11] compared the mechanical properties and microstructure of Ti-5111 plates welded by filler metal matching the base metal (BM) composition, filler metal modified with 60 parts per million (ppm) Y, and filler metal modified with 268 ppm Y when employing a gas-tungsten arc welding (GTAW) procedure. Their results indicated that the FZ of both yttrium-modified filler metal welds exhibited greater ductility (percent reduction in area) of  21.2 1.0 % and  17.4  6.4 %, when compared to the the FZ of the matching BM filler metal weld ductility of  14.8  7.5 % and the BM ductility of  15.0  3.3 % [11,12]. Additionally, Vickers microhardness measurements indicated that the FZ of both yttrium-modified filler metal welds exhibited a lower hardness when compared to the FZ of the matching BM filler metal weld [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of useful researches on the microstructure and mechanical properties of GTAW joint are conducted for the Titanium and its alloys [6][7][8]. However, very limited studies about the GTAW joint have been reported for the Ti6321 alloy.…”
Section: Introductionmentioning
confidence: 99%